An 11‐lncRNA expression could be potential prognostic biomarkers in head and neck squamous cell carcinoma. Issue 10 (29th May 2019) - Xu, Qingyong; Yin, Hang; Ao, Haijiao; Leng, Xue; Liu, Mingdong; Liu, Yang; Ma, Jianqun; Wang, Xiaoyuan
Abstract: The aim of our study is to construct the competing endogenous RNA (ceRNA) network of head and neck squamous cell carcinoma (HNSCC) and identify key long noncoding RNAs (lncRNAs) to predict prognosis. The genes whose expression were differentially in HNSCC and normal tissues were explored by the Cancer Genome Atlas database. The ceRNA network was constructed by the Cytoscape software. The lncRNAs which could estimate the overall survival were explored from Cox proportional hazards regression. There are 1997, 589, and 82 mRNAs, lncRNAs, and miRNAs whose expression were statistically significant different, respectively. Then, the network between miRNA and mRNA or miRNA and lncRNA was constructed by miRcode, miRDB, TargetScan, and miRanda. Five mRNAs, 10 lncRNAs, and 3 miRNAs were associated with overall survival. Then, 11‐lncRNAs were found to be prognostic factors. Therefore, our research analyzed the potential signature of novel 11‐lncRNA as candidate prognostic biomarker from the ceRNA network for patients with HNSCC. Abstract : The current study not only provides the competing endogenous RNA (ceRNA) molecular mechanisms, but also explored the potential of a novel 11‐lncRNA signature as a candidate biomarker for patients with head and neck squamous cell carcinoma (HNSCC).